FIELD EVALUATION OF FIPRONIL AND LAMBDA CYHALOTHRIN FOR THE CONTROL OF SUGARCANE LEAF HOPPER (PYRILLA PERPUSILLA) ON SUGARCANE - Salma Ashraf; Ayesha Aihetasham (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Sugarcane is the primary cash crop and the only source of sugar in Pakistan. The growing population has led to an increased demand for sugar, requiring higher yields of sugarcane. However, insect pests, such as Pyrilla perpusilla, pose a significant challenge to increasing yields and must be managed to reach production goals. An experiment was carried out in Pattoki, District Kasur to evaluate the effectiveness of chemical control on sugarcane leaf hopper, P. perpusilla. Sugarcane US-54 was planted in last week of March, 2022 and two insecticides, Fipronil -5 SC @ 2ml/lit. of water and Lambda Cyhalothrin- 2.5 EC @ 2ml/lit. of water were tested against an untreated control group using a randomized block design with three replicates. The results showed that both insecticides significantly reduced the infestation of leaf hoppers at 10, 15, and 30 days after treatment, leading to an increase in cane yield as compared to the control group. Lambda Cyhalothrin- 2.5 EC @ 2ml/lit. of water was found to be the most effective in controlling Pyrilla infestation among all the products tested